2020
DOI: 10.1097/sla.0000000000004106
|View full text |Cite
|
Sign up to set email alerts
|

Social Media Responses to Elective Surgery Cancellations in the Wake of COVID-19

Abstract: Objective: To assess public response to cancellations of elective surgeries following the American College of Surgeons' (ACS) recommendation on March 13. Methods: We queried text comments from Reddit, a social media platform and the fifth most popular website in the United States. Comments were manually reviewed to assess for relevance to elective surgery in the United States during the global coronavirus outbreak, whether the text was written by a healthcare worker (HCW), whether the user was based in the Uni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 2 publications
0
3
0
Order By: Relevance
“…12 The simple form of quantitative analysis used in our study does not provide sophisticated results compared to other social media study methods such as sentiment analysis. [13][14][15][16] Using sentiment analysis could have provided a deeper insight into the content of the social media posts that were examined. Another limitation concerns the way credentials such as Dr., M.D., and D.O.…”
Section: Limitationsmentioning
confidence: 99%
“…12 The simple form of quantitative analysis used in our study does not provide sophisticated results compared to other social media study methods such as sentiment analysis. [13][14][15][16] Using sentiment analysis could have provided a deeper insight into the content of the social media posts that were examined. Another limitation concerns the way credentials such as Dr., M.D., and D.O.…”
Section: Limitationsmentioning
confidence: 99%
“…While Twitter data have been used to identify experiences and opinions on COVID‐19 from the public (Ainley et al, 2021; Alomari et al, 2021; Babvey et al, 2021; Dyer & Kolic, 2020; Gao et al, 2021; Guntuku et al, 2020; Huang et al, 2020; Karami & Anderson, 2020; Koh & Liew, 2022; Lee et al, 2020; Lwin et al, 2020; Osakwe et al, 2021; Rao et al, 2020; Skalski et al, 2017; Su et al, 2020; Valdez et al, 2020) and USA medical professionals (Sullivan et al, 2021; Wahbeh et al, 2020), it has not been used to study the impact of the pandemic on the wellbeing of NHS GPs practising in the United Kingdom (Jefferson, Golder, et al, 2022). In a systematic review published in 2022, we identified 31 studies exploring the impact of COVID‐19 on primary care doctors' mental health and wellbeing; all of which relied upon traditional methods of data collection; namely surveys or interviews (Jefferson, Golder, et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Unsurprisingly, this has focused recently on issues related to COVID-19 and work practices [16]. Analysis of Twitter posts is used commonly to identify public experiences and opinions, including recently on COVID-19 and its impact [17][18][19][20][21][22][23][24][25][26][27][28][29][30][31].Medical professionals' opinions about COVID-19 have been studied using social media [32], but no studies to date have examined GP wellbeing using social media monitoring, which is the aim of this study.…”
Section: Introductionmentioning
confidence: 99%